FREQUENCY OF A1U) AND Rh(D) BLOOD GROUPS IN MARDAN (NWFP) - Mahbood, Neelam; Mohammad, Wisal; Mohammad, Khaista; Hussain, Talib; Banuri, Faiza (Journal of Ayub Medical College Abbottabad, 1993)
A survey of blood groups in Mardan was carried out between October, 1992 to May, 1993. A total of 3860 subjects were analyzed. The commonest blood group was B (34.9%) Blood group 0 was (32.4%). Group A was found to be 22.4% and AB 10.3%. Overall 94.7% of subjects were Rh(D) positive.